Uji Efektivitas Transdermal Patch Antipiretik Ekstrak Daun Dadap Serep (Erythrina Subumbrans (Hassk.) Merr) terhadap Mencit Putih (Mus Musculus) Model Hipertermia - Priolaningsih, Dhela Rahma; Susilowati, Arikha Ayu; Cahyaningrum, Yanuar As’hari (Berkala Ilmiah Kimia Farmasi, 2025)
Dadap serep leaves (Erythrina subumbrans (Hassk.) Merr) contained saponins, flavonoids, tannins, and alkaloids which had the potential to lower body temperature. This research aimed to formulate a stable transdermal patch of Dadap Serep Leaf Extract (EDDS) and evaluate this transdermal patch based on temperature changes in white mice (Mus musculus) hyperthermia models at 17, 20, and 40%. This research was an experimental laboratory with a pre- and post-test control group design to test the effectiveness of the EDDS transdermal patch. Evaluation of the patch used physical quality stability tests using the freeze-thaw method including organoleptic, weight uniformity, thickness, folding resistance, and pH. Then the effectiveness test of this EDDS transdermal patch was tested on a white mouse hyperthermia model. The treatment group consisted of positive control (marketed compress product), negative control (peptone induction), and transdermal patch with EDDS extract at 17, 20, and 40% for 2 hours with monitoring every 30 minutes. The results showed that the transdermal patch preparation had good stability after physical quality stability testing using the freeze-thaw method. It was concluded that the most effective EDDS transdermal patch formulation in reducing temperature in white mice was a concentration of 40% with a temperature reduction percentage of 84.5%.   Keywords:  Transdermal Patch, Hipertermia, Dadap Serep Leaves, Soxhletation, Freeze-thaw